PERSEPSI KEGUNAAN APLIKASI BRIMO DALAM MEMBERIKAN KEMUDAHAN LAYANAN BAGI NASABAH PT. BANK RAKYAT INDONESIA (Persero) Tbk. - Larasati Putria Ningrum, (2023)
M-Banking is a service that has been provided by banks with the aim of making it easier for customers to make transactions. BRI is one of the banks that provides the best M-Banking facilities for its customers, the M-Banking application is BRImo. BRImo provides various useful features for its users in providing convenience to customers. In this final project the author has a goal to be achieved to find out the results of the perception analysis of the usefulness of the BRImo application in providing easy service for customers. This final project uses qualitative research. Data collection in this final project is the customer of BRI Fatmawati Branch. Distribution of questionnaires from March 16 to May 5, 2023. The results of the questionnaires collected amounted to 68 respondents. From the results of the final assignment report it can be seen that the perception of each use of the BRImo application gives a good average score with an acquisition of 90.76% or the result value is at the level of 89-99.5, which means that the perception of BRImo application users provides convenience because almost all respondents answered very agree.